Safety and efficacy of outpatient continuous terlipressin infusion for the treatment of portal hypertensive complications in cirrhosis. Issue 2 (February 2022) - Gow, Paul J.; Sinclair, Marie; Thwaites, Phoebe A.; Angus, Peter W.; Chapman, Brooke; Terbah, Ryma; Testro, Adam G.
Abstract : Background/Aim: Therapeutic options are limited for patients with hepatorenal syndrome (HRS), diuretic refractory ascites and hepatic hydrothorax who are awaiting liver transplant. We assessed the safety and efficacy of continuous terlipressin infusion (CTI) for treating these conditions in an outpatient setting. Method: All patients treated with CTI from May 2013 through March 2018 at our institution were initiated in-hospital on bolus dose terlipressin therapy for 24−72 h prior to commencing CTI for home therapy. Daily home visits for clinical assessment and medication administration were provided. Adverse events, effects of treatment on renal function, model for end-stage liver disease (MELD) score, and paracentesis/thoracentesis requirements were assessed. Results: Twenty-three patients were included (HRS = 17; refractory ascites = 4; refractory hepatic hydrothorax = 2). Median (range) duration of outpatient CTI was 50 (1–437) days with a total of 2482 patient days of treatment. Fourteen patients (60.9%) received a liver transplant; of whom 13 (92.9%) were alive at the end of the study period. There were no cardiac or ischemic complications and no serious adverse events reported. In patients with HRS, median serum creatinine significantly decreased from 202.0 μmol/L at baseline to 125.5 μmol/L at day 14 of CTI ( P = 0.0003) and remained stable thereafter. Median MELD score decreased from 22.5 to 19.0 at end of CTI ( P = 0.008). Median frequency of paracentesis/thoracentesis was 4 per month prior to CTI versus 1.52 during treatment. Conclusion: Transplant-eligible and otherwise stable patients can be managed with CTI at home for an extended duration under supervision without adverse consequences.